Demographic, Mentorship Quality, Employability: Intern Satisfaction as Variable Mediation - Fauji, Moch Iqbal; Ruspitasari, Widi Dewi (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
The development of the modern world of work requires students to have practical skills relevant to industry needs. This study aims to determine the relationship between demographics and mentorship quality in influencing student internship satisfaction and Employability. In addition, this study aims to examine the role of internship satisfaction as a mediator between demographics and mentor quality at Infinite Learning company. This study was conducted using quantitative methods in the form of an online questionnaire with 121 respondents from the student intern population. This study was analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to evaluate the relationship between variables. The results of the analysis show that mentor quality has an effect on student internship satisfaction, and internship satisfaction has a significant impact on student employability. Mentor quality affects Employability through the mediation of internship satisfaction. However, demographic factors did not show a significant effect on internship satisfaction and Employability. Demographics had no effect on Employability through internship satisfaction as a mediating variable. This study emphasizes the importance of mentorship quality in improving internship experience and students' readiness to enter the job market. For further research, it is recommended to explore more deeply the factors that influence Employability outside the context of student internship by including information related to long-term career development. This more comprehensive approach is expected to provide more accurate information on the influence of various factors on interns' work readiness and improve the effectiveness of internship programs in the future.